COGNITION-GUIDE: genomics-guided targeted post-neoadjuvant therapy in patients with early breast cancer$dstudy design of a multicenter, open-label, umbrella phase II study = COGNITION-GUIDE : molekulare Diagnostik zur Stratifizierung der post-neoadjuvanten Therapie bei Patientinnen mit Brustkrebs im Frühstadium : Studiendesign einer multizentrischen Open-Label-Umbrella-Phase-II-Studie - Pixberg, Constantin Frederic; Maurer, Christian; Smetanay, Katharina; Strassl, Luise; Hlevnjak, Mario; Zapatka, Marc; Wagner, Celina; Yazdanparast, Haniyeh; Kurzawa, Johanna; Erben, Vanessa; Feng, Fangyoumin; Hong, Chen; et al. (Geburtshilfe und Frauenheilkunde, 2025)
Background As part of the COGNITION diagnostic registry program, residual tumor material after neoadjuvant therapy (NAT) of patients with early breast cancer (eBC), who are still at high-risk for relapse after NAT, is analyzed by next generation sequencing to identify biomarkers and actionable alterations. This strategy aims to stratify patients for subsequent genomics-guided therapies to reduce the significant risk of metastatic dissemination and hence to improve disease-free survival. Patients and Methods COGNITION-GUIDE is a multicenter umbrella phase-II-trial to translate molecular biomarker profiles generated in the COGNITION platform into six molecular-guided post-neoadjuvant therapeutic options in addition to standard-of-care treatment. Patients can be allocated to 1. immune checkpoint inhibition (PD-L1-antibody), 2. PI3K inhibition, 3. AKT inhibition, 4. PARP inhibition, 5. anti-Trop-2 antibody-drug-conjugate, 6. HER2 inhibition or, in case of missing biomarkers, to observation for 12 months. The primary endpoint is invasive disease-free survival (IDFS) four years after surgery. Secondary endpoints include IDFS in each study arm separately, distant disease-free survival, overall survival and safety. 240 patients will be enrolled within four years. Conclusions The COGNITION-GUIDE trial, which was activated in June 2023 and will recruit in different centers in Germany, empowers a risk-adapted, biomarker-guided therapy escalation algorithm in eBC patients who are still at high risk of metastasis.
Gesehen am 04.02.2026